(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Software plays a major role in almost embedded systems. The examples of such softwares are Life- saving systems used in medical, mission critical systems used in missiles, launching of any satellites etc. apart from the functional complexities of available softwares, reliability of software with embedded systems has become a serious concern. Various techniques and methods are being formulated to predict or estimate the quality of such embedded software system from its structure in terms of quality and other parameters like reliability, safety and performance. However, the results of these quantitative structures for evaluation of reliability depend on design-time estimates for a series of model parameters. To overcome this problem, this paper presents a new design-time architecture evaluation method that includes uncertainties of various parameters. It first analyses some of available reliability models and proposes a new software reliability model for estimating, measuring and controlling software reliability of embedded system where various different parameters need to be estimated .